Serum C1q/TNF-related protein 9 is not related to nonalcoholic fatty liver disease. (October 2018) - Zhang, Chi; Zhou, Nan; Qiu, Ping; Fu, Yuming; Liu, Zefa; Li, Hongxia; Yang, Xiangjun; Zhang, Lei
Highlights: This is the first study regarding the role of circulating CTRP9 in NAFLD. Serum CTRP9 level was not different among the ultrasonographic degrees of NAFLD. Serum CTRP9 was not independently associated with NAFLD. Serum CTRP9 was independently and positively associated with body mass index. Abstract: Aims: C1q/TNF-related protein 9 (CTRP9) is an adipokine mainly secreted by white adipose tissue and plays protective roles in energy metabolism. However, information regarding the role of CTRP9 in nonalcoholic fatty liver disease (NAFLD) is scarce. Here we aimed to ascertain the clinical relevance between circulating CTRP9 levels and NAFLD through a cross-sectional study. Methods: The study enrolled 82 NAFLD adults and 79 sex- and age-matched non-NAFLD controls. Serum CTRP9 was measured via ELISA method. Metabolic parameters were also determined. Results: Although serum CTRP9 level seems to be higher in NAFLD adults, there was no significant difference among the ultrasonographic degrees of NAFLD ( P = 0.275). Further, after adjustment for BMI in the multinomial logistic regression model, no significant odds ratio difference was observed for NAFLD among the CTRP9 tertiles. Moreover, binary logistic regression models demonstrated that, body mass index (BMI) and alanine aminotransferase (ALT) but not CTRP9 were independent factors related to NAFLD. Besides, serum CTRP9 was positively correlated with BMI, waist circumference, Fasting insulin, HbA1c, and HOMA-IR in all subjects. BMI was the independent factor associated with serum CTRP9. Conclusions: Serum CTRP9 is not independently related to NAFLD. The association between serum CTRP9 and NAFLD might be due to the influence of obesity.